The Yoga Sutra of Patanjali: A Biography, by David G. White - Powell, Seth (Religions of South Asia, 2018)
The Yoga Sutra of Patanjali: A Biography, by David G. White. Princeton, NJ: Princeton University Press, 2014. xvii + 273 pp., 24.95. ISBN 978-0-691-14377-4 (hb).